Use of multicomponent, domino, and other one-pot syntheses on solid phase: powerful tools for the generation of libraries of diverse and complex compounds - Pulici, M; Cervi, G; Martina, K; Quartieri, F (Combinatorial chemistry & high throughput screening, 2003)
The availability of small organic molecules covering as much chemical space as possible is seen as the only means that guarantees potential modulation of the many biological targets that are ultimately being unveiled by genomics. Therefore diversity oriented organic synthesis is rapidly becoming one of the paradigms in the process of modern drug discovery. This has spurred research in those fields of chemical investigation that lead to the rapid assembly of not only molecular diversity, but also molecular complexity. As a consequence multi-component as well as domino or related reactions are witnessing a new spring. Coupling these one-pot processes with solid-phase synthesis offers new perspectives for the preparation of both primary and thematic libraries. The progresses recently made in this field that perfectly suits the needs of modern drug discovery are the subject of the present review.